2018
DOI: 10.1186/s12887-018-1144-5
|View full text |Cite
|
Sign up to set email alerts
|

Augmentative and alternative communication in children with Down’s syndrome: a systematic review

Abstract: BackgroundThe use of technology to assist in the communication, socialization, language, and motor skills of children with Down’s syndrome (DS) is required. The aim of this study was to analyse research findings regarding the different instruments of ‘augmentative and alternative communication’ used in children with Down’s syndrome.MethodsThis is a systematic review of published articles available on PubMed, Web of Science, PsycInfo, and BVS using the following descriptors: assistive technology AND syndrome, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 64 publications
1
25
0
3
Order By: Relevance
“…Because of limitations in cognitive domains such as memory, concentration, learning, and communication, the learning progress proceeds more slowly in children with Down syndrome than in other children of the same chronological age [9,12]. Communication difficulties in children with Down syndrome result in their receiving instruction at a slower pace.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because of limitations in cognitive domains such as memory, concentration, learning, and communication, the learning progress proceeds more slowly in children with Down syndrome than in other children of the same chronological age [9,12]. Communication difficulties in children with Down syndrome result in their receiving instruction at a slower pace.…”
Section: Discussionmentioning
confidence: 99%
“…To prevent the occurrence of periodontal disease, the maintenance of oral hygiene is very important; however, because of their intellectual limitations, low IQ, and low memory, this activity is difficult for children with Down syndrome [8,9]. An educational toy aiming specifically at educating children with Down syndrome, such as the busy book, is needed.…”
Section: Introductionmentioning
confidence: 99%
“…In Polish population the adopted Makaton system uses graphic drawings, as well as gestures which support the verbal communication and serve as an additional means that strengthens the message transmission [23]. Apart from the manual signs, there are, graphic symbols which are applied in Makaton and that are used by people who are unable to make a gesture, then they indicate the symbol and in this way they signal their needs and interests [24]. Commonly, the mime as well as the pantomime constitute the techniques of presenting moods, feelings, emotions, certain activities, concrete and abstract issues through gestures, movements of the whole body, as well as the facial expressions [25].…”
Section: Examples Of Signs In Aac Systems Used In Polandmentioning
confidence: 99%
“…11 In our own review, we have previously concluded that is a valuable tool, because ASD children's interest is aroused by this technology, which they find attractive and motivating. 12,13 AR applications can stimulate problem-solving skills for cognitive empowerment in typically or atypically developing children, as well as promoting inclusion and social integration as would be desirable in educational and group rehabilitation settings. 14 Research into AR-based social skills for people with ASD has also reported positive findings.…”
Section: Introductionmentioning
confidence: 99%